Human rights from an Islamic perspective - Laluddin, Hayatullah; Mohd. Nor, Amir Husin; Moustafa Moursi el- Seoudi,, Abdel Wadoud; Ibrahim, Ibnor Azli; Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Samsudin, Muhammad Adib; Alias, Muhammad Nazir (2011)
A critical overview of human rights from western perspective reveals their deficiencies in conceptualization, flaws in formulation, and injustices in application. This all is due to political agendas, economic pressure and culturally biased viewpoints. They often serve the interests of certain organizations. As such they carry the residues of colonialism and imperialism. This is clear from the ongoing suppression and atrocities inflicted on poor and weak nations without any effective measures being taken by these organizations for their defense and protection. Double standard is applied when it comes to the violation of human rights. Weak states are vigorously pursued whereas, powerful are blatantly exempted from prosecution. Islam as a divine and universal guidance lies a comprehensive framework of values that embodies universal human rights, which is free of bias and deal with the abuser of the human rights equally regardless the race, religion and color factors, hence provides a universal criterion for human rights. Therefore, this paper attempts to analyze the issue of human rights from an Islamic perspective in the light of the purposes of the law, and delineate the mechanism for their protection. Using both descriptive and analytical methods the research concludes that Islam provides a comprehensive and practical mechanism for protection of human rights which is just and of universal application hence is the pioneer of human rights.